Taxonomic composition of epilithic diatoms and indicator role in freshwater pools and the effect of pollution in the Keban Dam lake, Turkey - Yildirim, Vesile; Demirkapu, Selda (Eduem - Editora da Universidade Estadual de Maringa, 2024)
The aim of this study is to determine the epilithic diatom flora of stations exposed to pollutants of different characteristics, to test the relationships of these diatoms with water quality and the suitability of environmental quality indicators, and to determine different indicators of various quality pollutants for the rapid assessment of ecological pollution. Additionally, determining the ecological impact of both industrial and domestic waste on the reservoir in the region and determining whether the diatom community changes when exposed to various pollutants (including potential mortality), especially its role as an indicator of metal pollution; Samples taken from stations where domestic and industrial wastes were discharged with different chemical properties were evaluated and investigated. A total of 100 species were identified for Bacillariophyta. Although there was no significant change in the number of the species among the stations, significant changes were observed in the community structure. While Achnanthidium minutissimum, Fragilaria capucina, Gomphonema parvulum, Nitzschia palea and Surirella angustatum were the dominant diatoms in the impermeable artificial pool where the industrial wastewater of the factory was collected, Nitzschia amphibia, N. palea, N. recta and Ulnaria ulna were the dominant diatoms of the station where domestic wastewater was discharged. In the dam area where domestic wastewater is discharged, Fragilaria capucina Ulnaria ulna and Diatoma vulgaris are the dominant diatoms. Achnanthidium minutissimum, Gomphonema parvulum Navicula cinta and Nitzschia amphibia, N. angustata were the dominant diatoms of the station where both domestic and industrial wastewater was discharged. It was determined that benthic diatoms responded to different types of waste by changing their species composition, and that the change in the benthic community was not due to seasonal differences in stations under the influence of pollutants with different chemical properties. Diatom taxa which are known to tolerate metal concentrations, diatom diversities, and teratologies were determined. © 2024, Eduem - Editora da Universidade Estadual de Maringa. All rights reserved.
Keywords: Dam lake; Diversity; Epilithic diatoms; Heavy metals; Pollution; Water quality